STUDI LITERATUR PENERAPAN PENDEKATAN STEAM TERHADAP PEMBELAJARAN KIMIA - Jovianto, Andrean (Jurnal Kajian Pembelajaran dan Keilmuan, 2026)
The STEAM (Science, Technology, Engineering, Art, and Mathematics) approach is a pedagogical framework centered on cultivating creative, innovative, and critical thinking, among other key 21st-century competencies. This study aims to determine the effective and optimal application of the STEAM approach within chemistry education. A Systematic Literature Review (SLR) was conducted, sourcing literature from Google, Google Scholar, and the Journal of Chemical Education. The methodology involved formulating research questions, devising a search strategy, applying inclusion and exclusion criteria, evaluating and analyzing the collected data, and reporting the subsequent findings. The results demonstrate that the implementation of the STEAM approach in chemistry education significantly enhances students' conceptual mastery, practical abilities, and creative, critical, and innovative thinking, as well as crucial collaboration and communication skills relevant to a globalized world. In conclusion, the adoption of the STEAM approach in chemistry education is demonstrably positive and beneficial for fostering both academic and soft skills in students.